VISITOR TRACKING MOBILE APPLICATION FOR NON LANDED AREAS - Maniam, Vihashinii Maniam (IRC, 2020)
The research topic is related to the improvement of communication between Security management in non-landed areas and their respective residents. Safety system is a very important factor in all residential areas especially when it comes to visitor tracking process. Visitor tracking technology provides an unparalleled level of insight which organisations have never had before using a traditional, paper-based system. Using a visitor management system, management will utilise full reporting functionalities. A benefit which is invaluable today, as insight from every corner of a business is examined to improve organisational efficiency. These instant reports, available from an intuitive safety system, give an extensive overview of who is in, out or expected at the premises. Further to this, these reports are available on mobile devices as an application , meaning security management and residents can access the reports anytime, anywhere. By going through all the information provided by the experts from the home safety field and statistics of usage in smartphone has become the backbone to propose this project paper to be developed into a prototype.